Assessing quality of life in patients with prostate cancer: a systematic and standardized comparison of available instruments. - Schmidt, S; Garin, O; Pardo, Y; Valderas, J; Alonso, J; Rebollo, P; Rajmil, L; Garcia-Forero, C; Ferrer, M (2014)
PURPOSE: The objective was to obtain a standardized evaluation of available prostate cancer-specific quality of life instruments used in patients with early-stage disease. METHODS: We carried out systematic literature reviews in the PubMed database to identify manuscripts which contained information regarding either the development process or metric properties of prostate cancer-specific quality of life instruments. Each instrument was evaluated by two experts, independently, using the Evaluating Measures of Patient-Reported Outcomes (EMPRO) tool. An overall and seven attribute-specific EMPRO scores were calculated (range 0-100, worst to best): measurement model, reliability, validity, responsiveness, interpretability, burden and alternative forms. RESULTS: Eight instruments and 57 manuscripts (2-15 per instrument) were identified. The Expanded Prostate Cancer Index Composite (EPIC) was the best rated (overall EMPRO score 83.1 points). Good results were also obtained by University of California Los Angeles-Prostate Cancer Index (UCLA-PCI), Patient-Oriented Prostate Utility Scale (PORPUS) and Prostate Cancer Quality of Life Instrument (PC-QoL) with 77.3, 70.5 and 64.8 points, respectively. These four instruments passed with distinction the validity and responsiveness evaluation. Insufficient reliability results were observed for UCLA-PCI and PORPUS. CONCLUSIONS: Current evidence supports the choice of EPIC, PORPUS or PC-QoL. Attribute-specific EMPRO results facilitate selecting the adequate instrument for every purpose. For longitudinal studies or clinical trials, where responsiveness is the priority, EPIC or PC-QoL should be considered. We recommend the PORPUS for economic evaluations because it allows cost-utility analysis, and EPIC short versions to minimize administration burden.